New species of the tribe Sericini Kirby, 1837 from China, with further updates on their taxonomy and distribution (Coleoptera: Scarabaeidae: Sericinae) - Zhao, Ming-Zhi; Ahrens, Dirk (Zootaxa, 2023)
Fifteen new species of Sericini are described from China, including Gastroserica (s. str.) mayunshui Zhao & Ahrens, new species, Pachyserica albopunctata Zhao & Ahrens, new species, P. dongnanensis Zhao & Ahrens, new species, P. jianfengensis Zhao & Ahrens, new species, Serica (s. l.) caiyiyiae Zhao & Ahrens, new species, S. (s. l.) babaoshanensis Zhao & Ahrens, new species, S. (s. l.) jicaiyanae Zhao & Ahrens, new species, S. (s. l.) zhangyaonani Zhao & Ahrens, new species, S. (s. l.) longidentata Zhao & Ahrens, new species, S. (s. l.) callosericoides Zhao & Ahrens, new species, S. (Taiwanoserica) liboyani Zhao & Ahrens, new species, S. (T.) yangzaichuni Zhao & Ahrens, new species, Maladera zhanchaoi Zhao & Ahrens, new species M. parabikouensis Zhao & Ahrens, new species and M. shikengkongensis Zhao & Ahrens, new species. Maladera juxianensis Ahrens, Fabrizi & Liu, 2021 was recognized as a junior synonym of M. aureola (Murayama, 1938). Additional collecting data for 32 other sericine species is presented.